2009
DOI: 10.3390/ijms10073224
|View full text |Cite
|
Sign up to set email alerts
|

The Evaluation of the Possibilities of Using PLGA Co-Polymer and Its Composites with Carbon Fibers or Hydroxyapatite in the Bone Tissue Regeneration Process – in Vitro and in Vivo Examinations

Abstract: Synthetic polymers belonging to the aliphatic polyester group have become highly promising biomaterials for reconstructive medicine. The purpose of the present work is a biological evaluation of lactide-glycolide co-polymer (PLGA) and its composites with carbon fibers (PLGA+CF) or hydroxyapatite (PLGA+HA). The cytotoxicity of the evaluated materials towards hFOB 1.19 human osteoblast-like cells was assessed. Moreover, during the one-year contact of the assessed materials with living osseous tissue, the progres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
23
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 26 publications
3
23
1
Order By: Relevance
“…2a). The bioactive activated carbon fibers are biocompatible and have been used to create 3D scaffolds for cell growth, proliferation, and adhesion in tissue engineering [20]. Figure 4 shows the morphology of RSF cells attached to the surface and interior pore space of activated carbon fibers at different times during cell culturing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2a). The bioactive activated carbon fibers are biocompatible and have been used to create 3D scaffolds for cell growth, proliferation, and adhesion in tissue engineering [20]. Figure 4 shows the morphology of RSF cells attached to the surface and interior pore space of activated carbon fibers at different times during cell culturing.…”
Section: Discussionmentioning
confidence: 99%
“…They are also used for the purification of various biofluids, including the cleansing blood of inflammatory mediators under conditions such as sepsis or remove cytokines interleukin-6 (IL-6), interleukin-8 (IL-8), and tumour necrosis factoralpha (TNF-a) [17][18][19]. Additionally, activated carbon fibers are biocompatible and bioactive, making them ideal for 3D scaffolds for cell growth, proliferation, or tissue engineering [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…The use of sequentially combined cell viability parameters during a cytotoxicity assay increases the chances of the detection of adverse effects and contributes to the refinement of the understanding of the mechanisms involved on toxicity (16). In this context, other studies of PLGA/HA composites found similar good cell viability by employing other non-metabolic assays, such as the LDH test with human hFOb 1.19 osteoblast-like cells (17), or through fluorescence-based LIVE-DEAD tests with RAW 264.7 murine macrophages (18). Moreover, the in vitro evaluation of biocompatibility of the PLGA/HA composite scaffolds Usually, during the development of novel biomaterials, in vitro results pointing to strong cytotoxic effects, such as those identified for the ReOss putty configuration (Fig.…”
Section: In Vitro and In Vivo Biocompatibility Of Reoss® Hydroxyapatitementioning
confidence: 97%
“…In the literature, favorable in vivo results were reported for the biological response for PLGA:HA composites as bone substitutes (13,17,20), as authors observed osteogenesis, and no inflammatory persistent reactions or osteolysis in implant sites. A PLGA/HA nanostructured composite, manufactured by baryosynthesis route, the same route described for the ReOss ® , resulted in a composite with enhanced biocompatibility and osteogenic properties compared to a similar composite fabricated by the solvent casting/particulate leaching process (3).…”
Section: In Vitro and In Vivo Biocompatibility Of Reoss® Hydroxyapatitementioning
confidence: 99%
“…Moreover, in their previous papers, the authors proved a stimulating effect of carbon fibres on the bone growth processes [17][18][19]. Moreover, in their previous papers, the authors proved a stimulating effect of carbon fibres on the bone growth processes [17][18][19].…”
Section: Introductionmentioning
confidence: 99%